The Influence of Gender and Learning Models on Students' Mathematical Reasoning Abilities at Students of Islamic Junior High School - Afrizal, Afrizal; Amry, Zul; Khairani, Nerli (UIN Sunan Gunung Djati Bandung, 2025)
This research is a quantitative research that aims to determine the effect of gender and learning models on students' mathematical reasoning abilities. The research was conducted at MTsS Madinatussalam Percut Sei Tuan using a quasi-experimental approach. This study involved students of grade VIII as participants selected through simple random sampling techniques. The research design used a 2Ã—2 factorial with two independent variables, namely discovery learning and conventional learning models and gender. The subjects of the study were class VIII-1 totaling 32 students as the experimental class and class VIII-2 totaling 32 students as the control class. The instrument used was a validated mathematical reasoning ability essay test. Data analysis was carried out using the Two-Way ANOVA test. The results of the analysis showed that: there was an effect of gender on mathematical reasoning abilities, there was an effect of learning models on mathematical reasoning abilities, and there was no significant interaction between gender and learning models on students' mathematical reasoning abilities. Thus, both gender and learning model individually influence students' mathematical reasoning abilities, but there is no combined interaction effect between the two